Structural study of β‐SiC(001) films on Si(001) by laser chemical vapor deposition. Issue 4 (4th January 2017) - Zhu, Peipei; Xu, Qingfang; Chen, Ruyi; Zhang, Song; Yang, Meijun; Tu, Rong; Zhang, Lianmeng; Goto, Takashi; Yan, Jiasheng; Li, Shusen
Abstract: β‐SiC thin films have been epitaxially grown on Si(001) substrates by laser chemical vapor deposition. The epitaxial relationship was β‐SiC(001){111}//Si(001){111}, and multiple twins {111} planes were identified. The maximum deposition rate was 23.6 μm/h, which is 5‐200 times higher than that of conventional chemical vapor deposition methods. The density of twins increased with increasing β‐SiC thickness. The cross section of the films exhibited a columnar structure, containing twins at {111} planes that were tilted 15.8° to the surface of substrate. The growth mechanism of the films was discussed.